Hubungan Pencahayaan, Lamanya Bermain Game Dan Sikap Kerja Dengan Kelelahan Mata Pada Atlet E-Sport PON Provinsi NTT - Dapa Tadi, Yuskariot; Umbu Roga, Anderias; Ruliati, Luh Putu (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
E-Sport athletes need expertise, accuracy and high concentration in playing games and when competing, if i t is continuously for a long time and monotonously and supported by work attitudesand unsupportive environmental conditions, it will be one of the causes of work fatigue. A work accident in question is an accidents that occur in a work environment which can be caused by unfavorable working environmental conditions. One of the accidents that can occur is eye fatigue. Eye fatigue is asymptom  of eye disorders  caused by excessive efforts of eye fuction for a long period of time and is accompanied by abnormal vision. The purpose of this research is to determine the linkages lighting, duration of playing games with work attitudes with complaints of eyestrain on E-Sport athletes at the National Sports Week on NTT Province. Research from with a cross sectional method. The numbers of samples in this study is namely 50 E-Sport athletes by means of sampling that used Total Sampling. Result obtained through filling out questionnaires by E-Sport athletes. Analysis of the data used is univariate with bivariate and using Chi Square test. The results from this study obtaened, that the variables of lighting (p=0.015), duration of playing games (p=0.025) and work attitude (p=0.519) have a relationship with eye fatigue. Based on the results of the research above, it can be concludedthat the work attitude variable has no relationship with eye fatigue, while the lighting variable and the length of playing the game have a relationship with eye fatigue in E-Sport PON NTT athletes